Eficiência econômica na produção de frangos de corte na região Centro-Oeste: uma análise estocástica - Zilli, Julcemar Bruno; Barros, Geraldo SantAna de Camargo (Revista Gestão da Produção Operações e Sistemas, 2006)
The broiler chicken farming has impressed by its dynamism and competence achieved across the last decades,highlighting Brazil as the second largest world producer. All technological advances have led the countrytowards the position of one the most efficient producers. However, significant specialization of this activitytends to exclude the minor poultry raisers and the less efficient farmers from the creative and productiveprocess. Thus, this study tried to measure the economic efficiency of broiler chicken farmers in the Braziliancentral-western region, by identifying which factors influence on this performance measurement. For thisreason, the stochastic profit frontier function in one stage (model 2) was used, in which the border coefficientsand the efficiency effects are simultaneously obtained, supposing that the error terms are not identicallydistributed. The coefficients indicated that a more intense use of family labor could increase the producersprofitability. A bigger profit in this activity is being indicated due to the fact that the region is relatively newand due to the existence of favorable conditions for capital and technology investment. Although a continuoustendency associated to the efficiency scale was not observed, there seems to be relevant efficiency gains in themedium and high production scale for the regional standards.Keywords: Economic efficiency; Inefficiency; Stochastic production function; Poultry raising; Rural producers.